2018
DOI: 10.1007/s00253-018-9181-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genetic tools for editing the genome of Riemerella anatipestifer using a counterselectable marker

Abstract: Riemerella anatipestifer (R. anatipestifer, RA) is an important bacterial pathogen of ducks and other birds; infection with RA causes high poultry mortality and heavy economic losses in the poultry industry. However, the pathogenesis of this bacterium is poorly understood, in part due to the lack of a suitable array of methods for genetic manipulation. In this study, we first examined the efficacy of the mutated pheS gene (pheS*) as a counterselectable marker in R. anatipestifer. A suicide vector carrying pheS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The competence machinery actively processes exogenous dsDNA and takes up internalized ssDNA to replace homologous (or partially homologous) chromosomal sequences via a mechanism catalyzed by RecA and facilitated by accessory factors, such as DprA (Kidane et al, 2012). Although it has been found that R. anatipestifer was natural competent and established multiple genome editing tools using it (Liu et al, 2018b), the mechanism of natural transformation in R. anatipestifer kept largely unknown. This study focused on the characterization of DprA in R. anatipestifer ATCC11845.…”
Section: Discussionmentioning
confidence: 99%
“…The competence machinery actively processes exogenous dsDNA and takes up internalized ssDNA to replace homologous (or partially homologous) chromosomal sequences via a mechanism catalyzed by RecA and facilitated by accessory factors, such as DprA (Kidane et al, 2012). Although it has been found that R. anatipestifer was natural competent and established multiple genome editing tools using it (Liu et al, 2018b), the mechanism of natural transformation in R. anatipestifer kept largely unknown. This study focused on the characterization of DprA in R. anatipestifer ATCC11845.…”
Section: Discussionmentioning
confidence: 99%
“…Transconjugants were shaken in GC broth (GCB) at 37 °C overnight to lose the suicide plasmid. Then, 200 μL of the appropriate dilution was plated on GCB agar supplemented with 13 mM p-Cl-Phe to select clones without the plasmid [27]. Clones were screened by PCR using primers cfx P1/P2 to choose Cfx-sensitive colonies.…”
Section: Methodsmentioning
confidence: 99%
“…The E . coli - Capnocytophaga canimorsus shuttle plasmid pMM47.A [29] was digested with PstI to remove the replication region and generate the plasmid pMM47.B, which has been constructed in previous study [24]. To increase the conjugation efficiency, oriT was amplified from the plasmid pEX18GM [30] using the primers oriTP1 (introducing a HindIII site) and oriTP2 (introducing a SphI site) (Table 2) and was cloned into pMM47.B to generate the plasmid pMM47.C.…”
Section: Methodsmentioning
confidence: 99%
“…The process of knockout based on pORS was done as described in previous study with a little modification [24]. Briefly, the 780-bp upstream sequence of RA0C_1534 was amplified using the primers RA0C_1534 upP1 (containing a NcoI site) and RA0C_1534 upP2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation